EXPERIMENTAL INVESTIGATION ON THE ABSORPTION CHARACTERISTIC OF CONCRETE PATCH REPAIR MATERIALS - Ashlembo, Nassr Omer Shahat; Kristiawan, Stefanus Adi; Rahmadi, Agus Parwito (Jurnal Teknik Sipil, 2015)
ABSTRACTStudying absorption of concrete patch repair material is very important for determining its durability and compatibility with concrete being repaired. The objectives of this research were: to determine the absorption of various repair materials and to assess the compatibility of these repair materials with concrete based on the absorption measurement. Absorption rate was determined based on ASTM C 1585-04. The result showed that unsaturated polyester resin-mortar (UPR-M) had the lowest rate of absorption measurement indicating that it is sufficient protection. The highest measurement values for rate of absorption was found for concrete with normal mortar repair material (NM) indicating that it did not provide sufficient protection.Â Keywords: absorption rate, concrete, patch repair materials